What has psychology ever done for British alcohol studies?. (2nd November 2017) - Cameron, Douglas
Abstract: Over the past forty years there have been significant changes in our ways of conceptualising and responding to people with alcohol problems. This paper provides a personal perspective upon what those changes have been and upon the role of psychologists in generating them. Further, it highlights the significant role played by a small multidisciplinary forum, The New Directions in the Study of Alcohol Group, in supporting workers move towards those changes particularly in the United Kingdom.